2009
DOI: 10.1128/aac.00056-09
|View full text |Cite
|
Sign up to set email alerts
|

Piperaquine Pharmacodynamics and Parasite Viability in a Murine Malaria Model

Abstract: Piperaquine (PQ) is an important partner drug in antimalarial combination treatments, but the long half-life of PQ raises concerns about drug resistance. Our aim was to investigate the extended antimalarial effect of PQ in a study of drug efficacy, reinoculation outcomes, and parasite viability after the administration of a single dose of PQ in the murine malaria model. Initially, male Swiss mice were inoculated with Plasmodium berghei and at 64 h after parasite inoculation were given PQ phosphate at 90 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…4). Consistent with our previous reports of piperaquine in the murine malaria model (43,44), high-dose CQ led to a curative response. This outcome occurred at very low plasma concentrations several weeks after dosing (the value was unable to be extrapolated from the present study but was likely Ͻ1 g/liter) (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…4). Consistent with our previous reports of piperaquine in the murine malaria model (43,44), high-dose CQ led to a curative response. This outcome occurred at very low plasma concentrations several weeks after dosing (the value was unable to be extrapolated from the present study but was likely Ͻ1 g/liter) (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Batty et al . have detailed the murine parasite time course after dihydroartemisinin , chloroquine or piperaquine treatment , and have demonstrated enhanced magnitude and duration of antimalarial killing following combination therapy or multiple dosing. The disposition of dihydroartemisin in mice has been described by a one compartment model, with a short elimination half‐life of ∼0.3 h .…”
Section: Models In Preclinical Evaluationmentioning
confidence: 99%
“…The key advantage of using P. berghei in murine models is that all erythrocytic stages of the parasite life cycle are observable in thin blood films and are easily differentiated by light microscopy (10). Thus, murine malaria studies can generate robust PK-PD data, as has been reported for dihydroartemisinin (DHA) (14,15), chloroquine (16), and piperaquine (17), which could be used to optimize dosing. However, traditional animal studies do not allow the evaluation of all doses and are unable to dissect immune elimination of parasite or the contributions of individual antimalarials in combination therapy.…”
mentioning
confidence: 92%